RECOGNITION DESIGN OF LICENSE PLATE AND CAR TYPE USING TESSERACT OCR AND EmguCV - Herusutopo, Antonius; Zuhrudin, Rizky; Wijaya, Willy; Musiko, Yuka (CommIT (Communication and Information Technology) Journal, 2012)
The goal of the research is to design and implement software that can recognize license plates and car types from images. The method used for the research is soft computing using library of EmguCV. There are four phases in creating the software, i.e., input image process, pre-processing, training processing and recognition. Firstly, user enters the car image. Then, the program reads and does pre-processing the image from bitmap form into vector. The next process is training process, which is learning phase in order the system to be able recognize an object (in this case license plate and car type), and in the end is the recognition process itself. The result is data about the car types and the license plates that have been entered. Using simulation, this software successfully recognized license plate by 80.223% accurate and car type 75% accurate.Keywords: Image; Pre-Processing; License plate and Car Type Recognition, Training